DEVELOPMENT OF INSTITUTIONAL MODELS OF INTELLECTUAL PROPERTY RIGHTS PROTECTION IN FOREIGN COUNTRIES - Zufarova Sh. M. (The American Journal of Political Science Law and Criminology, 2022)
The article provides an overview of the key institutional models for the protection of intellectual property rights in foreign countries. Three basic models of protection are justified in this articles. Special aspects of the activities of authorized administrative and law enforcement authorities of foreign countries to protect intellectual property are reviewed in this article. Recommendations for improving the institutional system for the protection of intellectual property rights in the Republic of Uzbekistan were developed based on the analysis.